2011
DOI: 10.4028/www.scientific.net/amr.331.165
|View full text |Cite
|
Sign up to set email alerts
|

Surface Deposition of Chitosan on Wool Substrate by Electrospraying

Abstract: Electrospraying or electrohydrodynamic spraying is a technique of liquid atomisation by utilising electrical forces. In the electrospraying technique, the liquid at the outlet of a nozzle is subjected to an electrical shear stress by maintaining the nozzle at high electric potential. This produces a fine mist of extremely small and in some cases down to nanometer size droplets. The charge and size of the droplets can be controlled by adjusting the flow rate and voltage applied to the nozzle. Extending the scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Liquid drops split into tiny droplets before depositing on the substrate. [20][21][22][23] Electrospraying has been used widely in areas such as ink-jet printing, [24,25] fabric functionalization, [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] making biomimetic materials, [42,43] and fabricating fuel cells. [44] Since the deposition rate can be controlled through adjusting the flow rate of liquid, electrospraying offers opportunities to control the coating depth on fabric, which is useful for making directional water fabrics.…”
Section: Doi: 101002/admi201600036mentioning
confidence: 99%
“…Liquid drops split into tiny droplets before depositing on the substrate. [20][21][22][23] Electrospraying has been used widely in areas such as ink-jet printing, [24,25] fabric functionalization, [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] making biomimetic materials, [42,43] and fabricating fuel cells. [44] Since the deposition rate can be controlled through adjusting the flow rate of liquid, electrospraying offers opportunities to control the coating depth on fabric, which is useful for making directional water fabrics.…”
Section: Doi: 101002/admi201600036mentioning
confidence: 99%
“…A high voltage is supplied to the solution in the needle. Due to the identical charge the droplets repel each other, then due to instability at the needle tip the droplets start dispersing into micron-sized particles and are deposited on oppositely charged surfaces, while the solvent is evaporated rapidly [20]. The method of producing chitosan nanoparticles through emulsion droplet coalescence is described in Figure 8.…”
Section: Process Technologies For Producing Chitosan Compositesmentioning
confidence: 99%
“…CHT has also been utilised for achieving anti-felting properties of wool [19]. Recent studies reported successful coating of CHT on wool nonwoven using electrospraying technique and pad-dry-cure method [20,21]. Thecurrent study reports paddingof CHTontothe 100% wool nonwoven matrix developed, followed by an evaluation ofblood uptake and antimicrobial properties related to wound dressing.…”
Section: Introductionmentioning
confidence: 96%